Acute kidney injury: risk factors and management challenges in developing countries - Ponce D; Balbi A (International Journal of Nephrology and Renovascular Disease, 2016)
Daniela Ponce, Andre Balbi Department of Medicine, Botucatu School of Medicine, Sao Paulo, Brazil Abstract: Acute kidney injury (AKI) is a major global health problem in both developed and developing nations, negatively affecting patient morbidity and responsible for an estimated 1.4 million deaths per year. Although the International Society of Nephrology set a goal of eliminating preventable deaths from AKI by 2025, implementation of this program in developing countries presents major challenges not only because of the lack of resources but also because of the scarce data addressing the epidemiology and causes of AKI in developing countries, the limited health care resources to diagnose and treat AKI, and the poor awareness of the impact of AKI on patient outcomes. Keywords: acute kidney injury, developing world, treatment